(untitled) (Journal of Science and Technology, 2016)
Between 1979 and 1985, several attempts were made by the Government of Ghana to restrict the number of makes and models of motor vehicles imported into Ghana. It was thought that a policy of motor vehicle standardisation would help to ease the problems associated with the procurement of spare parts for the vehicle fleet. However, implementation of this standardisation policy turned out to be very difficult. In this paper some of the many complex problems, of motor vehicle standardisation are discussed. It is argued that a standardisation policy would be too difficult to implement and would be of little benefit to the country. Instead of pursing a standardisation policy, which gives undue weight to the problem of spare parts availability, it would be more profitable to address the broader question of how best to improve road transportation in Ghana. This viewpoint leads to a number of suggested measures which, it is argued, are easier to apply and have a better chance of improving road transportation in Ghana.